IMPROVING THE ABILITY TO DESIGN CORE ACTIVITIES IN THE LEARNING PROCESS THROUGH ACADEMIC DEVELOPMENT FOR TEACHERS OF SDN 4 TELUK, BANYUMAS - Sachriyah, Siti; Abubakar, Wakhudin; Thoe, Ng Khar (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
Abstract. This study aims to improve the ability of teachers in designing core activities in the learning process through academic coaching. This research is motivated by the low ability to design core activities in the learning process of SD Negeri 4 Teluk teachers and the need for efforts to improve the ability to design these core activities through academic guidance. The method used in this research is comparative description. Collecting data using observation techniques, interviews, documentation, and filling out the instrument sheet. The research population in this study were 6 classroom teachers at SD Negeri 4 Teluk, namely grade 1 to grade 6 teachers. The results of this study indicate an increase in the ability of teachers to design core activities in the learning process .